2022
DOI: 10.1177/09544070221135445
|View full text |Cite
|
Sign up to set email alerts
|

Heating performance of heat pump air conditioning system for battery electric vehicle with different refrigerants

Abstract: To improve the heating performance of Heat Pump Air Conditioning System (HPACS) of Battery Electric Vehicle (BEV) and reduce the greenhouse effect of refrigerants, the performances of multiple refrigerants in different modes and conditions are analyzed in this paper. Based on Worldwide Harmonized Light Vehicles Test Cycle (WLTC) dynamic conditions, the impact of heating on battery State of Charge (SOC) is analyzed in HPACS and Positive Temperature Coefficient (PTC) combined heating mode. To better evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…They found that R1234yf yielded a result similar to that of R134a, but R744 performed worse than R134a. Li et al [19] analyzed heating performance with different refrigerants by simulating an electric vehicle heat pump system; they found that R32 showed an optimal COP and relatively little carbon emissions.…”
Section: Introductionmentioning
confidence: 99%
“…They found that R1234yf yielded a result similar to that of R134a, but R744 performed worse than R134a. Li et al [19] analyzed heating performance with different refrigerants by simulating an electric vehicle heat pump system; they found that R32 showed an optimal COP and relatively little carbon emissions.…”
Section: Introductionmentioning
confidence: 99%